Knowledge of hypertension and its therapy in lay people - Simatupang, Abraham; Sitompul, Fransiska; Kurniaty, Linggom; Djojosaputro, Mulyadi; Lumbantobing, Romauli; Silaban, Hertina (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Hypertension is one of the non-communicable diseases that is becoming a global health problem. Hypertension can be identified by systolic blood pressure of 140 mmHg and diastolic 90 mmHg . Uncontrolled hypertension can lead to complications such as stroke, ischemic heart disease, heart attack, heart failure, kidney failure, blindness, etc. According to Basic Health Research 2018 ( Ris et Kesehatan Dasar 2018/Ris kesdas 2018) the prevalence of hypertension for >18 years old wa s 8.4%, and through measurements taken in health care facilities by 34.1%. Prevalence in the city was 34.4%, in the village was 33.7%, while according to gender 31.3% f or male and 36.9% for female. The study aimed to find out the knowledge and awareness of laypeople on hypertension and its therapy. This was a cross-sectional online study with 11 questions. Respondents were recruited from social media groups. The results showed 5 00 respondents (62.8 % female and 37.2 % male) involved in this study . The most common age range was 21-40 years (36.2 %), followed by 41-55 years (38.2%) , and the least was 56-65 years old (18.4%). Seventy-two percent of respondents did not have hypertension, and 9% said they did not know. Fifty-three percent of respondents knew about the value of high blood pressure, and 89% of the respondents said hypertension should be treated regularly. The most hypertension complications answered by respondents were stroke (40%), heart attack (26%) , and heart failure (16%). Amlodipine was the most mentioned by the respondents, and the second was ACE-inhibitor. However, omeprazole and omega-3 were also mentioned as anti-hypertension. Genetic s and a high salt diet were risk factors that many respondents chose. In conclusi on, the r espondents have a good understanding of hypertension. Information related to behaviour is needed to discontinue the increasing prevalence.